CAIN AND ABEL MOTIVE IN THE STORY “EIN BRUDERMORD IM ALTWASSER” BY GEORG BRITTING - Kadir Albayrak; Hatice Genç (Zeitschrift für die Welt der Türken, 2015)
Cain killing his brother Abel, the first homicide was committed and this incident is evidence that humankind can move over to the dark side by their ego taking a beating. Also, the homicide that Cain committed is recognized as the very beginning of the other misdeeds which have always existed and changed, evolved and grown in humankind in the course of time. As far as the incident which happened between two brothers narrated in the holy books, it is observed better with the perspective of today over the past that Human is such a creature that He is capable of doing any evil. The dilemma of good and evil reflected by the characters of Cain and Abel and the other conflicts stemming from this dilemma were such great inspirations among writers. Particularly, The Ancient Greek and JudeoChristian culture which lay foundation of the Western Europe Literature were adapted for the works of the western writers in various ways. In this study, we have attempted to interpret “Murdering the brother”, being one of those themes in the story of “Ein Brudermord im Altwasser” by Georg Britting.